PENGARUH AJARAN TAMANSISWA TRI NGA DAN MACHIAVELLIAN TERHADAP KEINGINAN MAHASISWA MELAKUKAN PENGGELAPAN PAJAK - Wardani, Dewi Kusuma; Baity, Haya Nur (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine the influence of tamansiswa tri nga and machiavellian teachings on students' desire to commit tax evasion. The population taken was all students in Indonesia with a sample of 287 respondents. The data collection technique in this research was carried out by distributing questionnaires. The data analysis method used is multiple linear regression with the help of SPSS 25 software. Based on the research results, it shows that understanding tamansiswa tri nga teachings has a negative effect, while machiavellian has a positive effect on students' desire to commit tax evasion.